(untitled) (Fiep Bulletin - online, 2014)
It aimed to identify time of practice and characteristics related to training and injuries incidence in sportive shooters. 72 athletes of “Santa Catarina Open Games” participated of this study. A mixing questionnaire elaborated by the National Center of Sports Excellency for the national project “Champion’s Profile” was used as instrument. Data were analyzed through descriptive statistics. The average age athletes started to practice was 24 years and practice time was about 13±11 years. Regarding training characteristics most of athletes carry out 3 sessions per week and average duration of each session is 2 hours. Only 11 subjects (15,3%) carry out complementary training sessions (lift weighting) and apparently they are not specific-oriented to modality. 19 subjects (26,4%) are used to carry out regular tests in order to evaluate physical condition. Most of athletes (54,2%) are oriented by coaches during training sessions and 66,7% of them receive any kind of financial assistance (equipment/material assistance was the most related one, with 68,8% of occurrence). Subjects evaluated the quality of personal equipment, accessory equipments and place of training as “good”, “very good” and “excellent”. Five subjects (6,9%) presented injury related to the modality in the past. The injured body regions were elbow and shoulder; reported diagnoses were luxation, subluxation, impact syndrome and tendonitis. 3 subjects (4,2%) reported they were injured at the competition and the affected body regions were the knee, elbow and shoulder; reported diagnoses were tendonitis and impact syndrome.